Difference between LABD of childhood and LABD of adults. - Jablonska, S.; Chorzelski, T. (European Journal of Pediatric Dermatology, 2018)
Chronic bullous disease of childhood is the infantile counterpart of linear lgA bullous disease of adults. The literature data and personal experience of the Authors do not provide conclusive evidence for the distinctness of the childhood and adult form of linear lgA bullous dermatosis. The clinical, histological and immunopathological characteristics and the response to the treatment with sulfones associated with small doscs of stcroids are similar or identical.